Redesign of the System for Evaluation of Teaching Qualities in Anesthesiology Residency Training (SETQ Smart). (November 2016) - Lombarts, Kiki M. J. M. H.; Ferguson, Andrew; Hollmann, Markus W.; Malling, Bente; Arah, Onyebuchi A.; Berger, M. M.; van Gessel, E.; Hoff, R.; Houweling, P.; Loer, S.; Padosch, S. A.; Schramm, M. J.; et al.
Abstract : Background: Given the increasing international recognition of clinical teaching as a competency and regulation of residency training, evaluation of anesthesiology faculty teaching is needed. The System for Evaluating Teaching Qualities (SETQ) Smart questionnaires were developed for assessing teaching performance of faculty in residency training programs in different countries. This study investigated (1) the structure, (2) the psychometric qualities of the new tools, and (3) the number of residents' evaluations needed per anesthesiology faculty to use the instruments reliably. Methods: Two SETQ Smart questionnaires—for faculty self-evaluation and for resident evaluation of faculty—were developed. A multicenter survey was conducted among 399 anesthesiology faculty and 430 residents in six countries. Statistical analyses included exploratory factor analysis, reliability analysis using Cronbach α, item-total scale correlations, interscale correlations, comparison of composite scales to global ratings, and generalizability analysis to assess residents' evaluations needed per faculty. Results: In total, 240 residents completed 1, 622 evaluations of 247 faculty. The SETQ Smart questionnaires revealed six teaching qualities consisting of 25 items. Cronbach α's were very high (greater than 0.95) for the overall SETQ Smart questionnaires and high (greater than 0.80) for the separate teaching qualities. Interscale correlations were all within the acceptable range of moderate correlation. Overall, questionnaire and scale scores correlated moderately to highly with the global ratings. For reliable feedback to individual faculty, three to five resident evaluations are needed. Conclusions: The first internationally piloted questionnaires for evaluating individual anesthesiology faculty teaching performance can be reliably, validly, and feasibly used for formative purposes in residency training. Abstract : System for Evaluation of Teaching Qualities Smart questionnaires were developed and validated for assessing teaching performance of faculty in residency training programs in different countries through a multicenter survey. System for Evaluation of Teaching Qualities Smart scores correlated with global ratings and yielded reliable feedback from three to five resident evaluations, thus providing a validated tool for international resident teaching assessment.